АЛЬТЕРГЛОБАЛЬНІ ПЕРЕДУМОВИ РОЗВИТКУ СВІТОВОЇ ТОРГІВЛІ (Світ фінансів, 2017)
Зварич Р. Є. Альтерглобальні передумови розвитку світової торгівліті. Розкрито феномен декомпартменталізації ринків, його вплив на взаємозалежність суб’єктів та місце в трансфертній комерційній політиці. Здійснено оцінку ринкової волатильності, проаналізовано жорсткі умови фінансування та фактори їх коливання. Визначено рівень цін на сировинні товари, виокремлено ринки їх перенасичення та перспективність до зростання. Встановлено тенденції ведення глобальної торгівлі та аргументовано напрями її розвитку. Досліджено різновекторний вплив глобальної торгівлі на країни, аргументовано реконфігурацію торгововиробничої моделі в альтерглобальних передумовах розвитку світової торгівлі. Зварич Р. Е. Альтерглобальные предпосылки развития мировой торговли. Раскрыт феномен декомпартментализации рынков, его влияние на взаимозависимость субъектов и место в трансфертной коммерческой политике. Проведена оценка рыночной волатильности, проанализированы жесткие условия финансирования и факторы их колебания. Определен уровень цен на сырьевые товары, выделены рынки их перенасыщения и перспективность к росту. Установлены тенденции ведения глобальной торговли, аргументированы направления ее развития. Исследовано разновекторное влияние глобальной торговли на страны и аргументировано реконфигурацию торгово-производственной модели в альтерглобальных предпосылках развития мировой торговли. Zvarych R. Alterglobal drivers of world trade development. Introduction. Globalization does not soften but increases global inequality and create more trade and economic opportunities for large industrial companies. Large corporations for better understanding the environment, development synergy, risk distribution and cost reducing should provide own corporate identity and social responsibility to society. So, development and implementation the program of transformations is actual today and should be alternative and global.Purpose. Purpose of the article is research the status decompartmentalisation of markets; evaluation the impulses of volatility and terms of financing; analysis of commodity prices; determination the strength of global trade and its differently directed impact on the countries.Methods. The method of content formalization the decompartmentalisation of markets is used; hypothetical-deductive method in evaluating the impulses of volatility and terms of financing is used; systematic approach to analyze commodity prices and strength of global trade is used; hypothesis method for reconfiguration of the commercial and industrial imagination to alterglobal drivers of world trade development is used.Results. Globalization is not an absolutely special, modern, and maybe the highest stage of integration. Decompartmentalisation of markets expands the scope of industrial and commercial opportunities, but at the same time imposes numerous restrictions on companies, limiting their autonomy and independence. Financial markets had a turbulent start of the year, reflecting concerns for the global economic outlook, amplified by a sudden repricing of credit risks. The weakness of commodity prices, especially for energy, persisted into 2016, pushing some prices to new lows at the start of the year. Global merchandise trade growth reached a post-crisis low in 2015, largely reflecting a marked deceleration in import demand from commodity exporters and slowing activity and economic rebalancing in China. Globalization increases the gap of economic and social development between rich and poor countries; deepens social stratification, technogenic congestion and environmental degradation; weakens the national economy.Conclusion. Lingering weakness in global merchandise trade diminishes the scope for productivity gains through increasing specialization and diffusion of technologies in global value chains. A shortening of global supply chains towards regional ones could accentuate this process. The trend towards rising food prices and growing food insecurity – which is mainly due to the neglect of agriculture over the last three decades – may be exacerbated by an attempt to solve climate problems through mitigation policies that encourage the reallocation of land to biofuel crops, while in the meantime the rise of temperatures and sea level will affect agricultural yields. Alternative approaches to economic policy can provide the progress of human development in all its aspects. An important task of alterglobalization is reconfiguration of trade and production imagination and conceptualization of social change.